(untitled) (World Economics and Finance Bulletin, 2024)
The insurance industry is innovating. Business models, services and processes are rapidly evolving, largely backed by technological developments. The particular historical context of COVID-19 provides a suitable case to understand the relevance of exploiting technology to react quickly to traditional and emerging risks. Focusing on the initiatives put in place by the most influential insurance companies at the global level, we have framed the innovation mechanisms in the industry, highlighting four rationales underpinning these initiatives (Adaption, Expansion, Reaction and Aggression), which differ according to the relevance of the technology in use and innovation to the portfolio of risks covered. Overall, it emerges that insurance companies have the room and capability to innovate, in many cases using technological applications to cover new and existing risks